2008
DOI: 10.1590/s0101-31222008000200006
|View full text |Cite
|
Sign up to set email alerts
|

Potencial alelopático do capim-annoni-2 (Eragrostis plana Nees) na germinação de sementes de gramíneas perenes estivais

Abstract: RESUMO -Das estratégias adotadas pelas plantas invasoras para dominância em comunidades vegetais a liberação de aleloquímicos se sobressai. Estes compostos encontram-se em qualquer parte vegetal, principalmente em exsudatos de raízes, folhas e seus degradados sendo liberados no ambiente através de emanações voláteis ou solúveis, translocados em água. O capim-annoni-2, Eragrostis plana Nees, é uma Poaceae exótica, invasora de pastagens e com potencial alelopático. Para testar este efeito coletaram-se caules e f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 6 publications
3
32
0
10
Order By: Relevance
“…At the vegetative stage, probably because the time between the applications of N and the harvest was the shortest, there was no difference 5 among doses. In the tough lovegrass that was not fertilized with N, Alfaya et al (2002) The allelopathic effect of the aqueous extracts on lettuce was visually observed (Figure 3) and quantified according to the germinability and the GSI (Table 2), in accordance with other authors who evaluated the allelopathic potential of the tough lovegrass (Ferreira et al, 2008;Favaretto et al, 2011). The allelopathic symptoms, in a greater or a lesser degree and depending of the extract, included necrosis, shortening and winding of the root apex (Figure 3), which is commonly reported in bioassays of this type (Souza Filho et al, 1997).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…At the vegetative stage, probably because the time between the applications of N and the harvest was the shortest, there was no difference 5 among doses. In the tough lovegrass that was not fertilized with N, Alfaya et al (2002) The allelopathic effect of the aqueous extracts on lettuce was visually observed (Figure 3) and quantified according to the germinability and the GSI (Table 2), in accordance with other authors who evaluated the allelopathic potential of the tough lovegrass (Ferreira et al, 2008;Favaretto et al, 2011). The allelopathic symptoms, in a greater or a lesser degree and depending of the extract, included necrosis, shortening and winding of the root apex (Figure 3), which is commonly reported in bioassays of this type (Souza Filho et al, 1997).…”
Section: Resultssupporting
confidence: 84%
“…The success of this species in colonizing extensive rural and ruderal areas is attributed, in part, to its allelopathic action (Ferreira et al, 2008;Favaretto et al, 2011). Recent studies have indicated the presence of phenolic compounds in the roots and leaves of this grass (Favaretto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This alien African grass is the most abundant and aggressive invasive plant in the Pampa Biome, responsible for causing widespread economic impacts on livestock by modifying the structure of plant communities and by affecting ecological balances. The heterotoxicity of tough lovegrass was been observed in bioassays of seed germination with white clover (Trifolium repens), Italian ryegrass (Lolium multiflorum), African bristlegrass (Setaria sphacelata), and bahiagrass (Paspalum notatum) (Coelho, 1986;Ferreira et al, 2008;Favaretto et al, 2011). However, it was assumed that tough lovegrass may also display autotoxicity, because in the field, the clumps are separated from each other by empty spaces with bare soil radius of 5-10 cm (Coelho, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation communities under this condition sustain larger amounts of green forage mass, accumulate dead and senescent material, eliminate soil open gaps, reduce the light penetration and the soil temperature on the soil surface. Together, these factors induce the allelopathic effect on the superficial soil layer or on South African lovegrass itself (Coelho, 1986;Ferreira et al, 2008), which, according to Mohler (2001), are harmful to seed germination and plant recruitment. On the contrary, the greatest invasion occurred under continuous grazing, regardless of the initial soil disturbance, and it was directly associated with a lower height of the native pasture imposed initially by the intensive grazing and, subsequently, maintained low by continuous grazing.…”
Section: Resultsmentioning
confidence: 99%